Maxillary reconstruction with bone transport distraction and implants after partial maxillectomy (2013)
Maxillary and mandibular bone defects can result from injury, congenital defect, or accident, or as a consequence of surgical procedures when treating pathology or defects affecting jaw bones. The glandular odontogenic cyst is an infrequent type of odontogenic cyst that can leave a bony defect after being treated by aggressive surgical means. First described in 1987 by Padayachee and Van Wyk, it is a potentially aggressive entity, having a predisposition to recur when treated conservatively, with only 111 cases having been reported hitherto. Most reports emphasize its clinical, radiographic, and histologic features, including a few considerations on rehabilitation for these patients. The aim of this article is to present the case of a 24-year-old male patient who, in 2001, was diagnosed with a glandular odontogenic cyst and to focus on the surgical approach and rehabilitation scheme. We performed an anterior partial maxillectomy. The osseous defect was treated using bone transport distraction. Dental and occlusal rehabilitation was achieved with titanium implants over transported bone and an implant-supported overdenture. A 9-year follow-up shows no evidence of recurrence of the pathology, adequate shape and amount of bone, functional occlusal and dental rehabilitation, and patient’s satisfaction.